Cell-autonomous clock of astrocytes drives circadian behavior in mammals - Brancaccio,M; Edwards,MD; Patton,AP; Smyllie,NJ; Chesham,JE; Maywood,ES; Hastings,MH (Science, 2019)
Circadian (~24-hour) rhythms depend on intracellular transcription-translation negative feedback loops (TTFLs). How these self-sustained cellular clocks achieve multicellular integration and thereby direct daily rhythms of behavior in animals is largely obscure. The suprachiasmatic nucleus (SCN) is the fulcrum of this pathway from gene to cell to circuit to behavior in mammals. We describe cell type–specific, functionally distinct TTFLs in neurons and astrocytes of the SCN and show that, in the absence of other cellular clocks, the cell-autonomous astrocytic TTFL alone can drive molecular oscillations in the SCN and circadian behavior in mice. Astrocytic clocks achieve this by reinstating clock gene expression and circadian function of SCN neurons via glutamatergic signals. Our results demonstrate that astrocytes can autonomously initiate and sustain complex mammalian behavior.